Another disaster foretold?: the case of the Child Support Agency - Roberts, Colette M. (1998)
The Child Support Agency became operational in April 1993. The government hoped to introduce a system which would be clear and consistent and would deliver realistic amounts of child maintenance from more absent parents than under the old court and Department of Social Security systems. In so doing, the new system would reduce animosity between parents by removing child maintenance from any other divorce or separation negotiations and applying a fixed formula.